Production potential of groundnut (Arachis hypogaea) based intercropping system as influenced by different levels of irrigation - HUSSAINY, SYED ABUL HASSAN; VAIDYANATHAN, R (The Indian Journal of Agricultural Sciences, 2020)
A field experiment was conducted at Oilseeds Research Station, Tindivanam during 2017–18 to evaluate the production potential of groundnut (Arachis hypogaea L.) based intercropping under different levels of irrigation. Groundnut when grown in intercropping systems can provide scope for improving the productivity and monetary return per unit area per unit time. As different crops have different water requirement which could be a main hurdle in intercropping system, the present study was conducted to identify the consumptive water use, water use efficiency and water productivity under intercropping system. Study revealed that, groundnut intercropped with blackgram was superior in number of nodules/plant, root depth and root volume and registered yield of 10.5% over sole crop of groundnut. Irrigation scheduling at 0.50 IW/CPE ratio recorded higher root depth and root volume but, yielded 26.5 and 18.4% lesser over IW/CPE ratio of 0.75 and 1.0, respectively. Higher net return and B: C ratio was recorded in groundnut + blackgram intercropping system with 0.75 IW/CPE ratio. The soil moisture extraction pattern varied under different intercropping systems and the frequency of irrigation. Groundnut + blackgram intercropping system utilised lesser consumptive water compared to the sole crop. Thus, from the study it may be inferred that, groundnut + blackgram intercropping system with irrigation scheduling at 0.75 IW/CPE ratio enhances the productivity with better water use efficiency and water productivity.